Deep Tumor Penetration of Doxorubicin-Loaded Glycol Chitosan Nanoparticles Using High-Intensity Focused Ultrasound - Choi, Yongwhan (Pharmaceutics, 2020)
The dense extracellular matrix (ECM) in heterogeneous tumor tissues can prevent the deep tumor penetration of drug-loaded nanoparticles, resulting in a limited therapeutic efficacy in cancer treatment. Herein, we suggest that the deep tumor penetration of doxorubicin (DOX)-loaded glycol chitosan nanoparticles (CNPs) can be improved using high-intensity focused ultrasound (HIFU) technology. Firstly, we prepared amphiphilic glycol chitosan-5β-cholanic acid conjugates that can self-assemble to form stable nanoparticles with an average of 283.7 ± 5.3 nm. Next, the anticancer drug DOX was simply loaded into the CNPs via a dialysis method. DOX-loaded CNPs (DOX-CNPs) had stable nanoparticle structures with an average size of 265.9 ± 35.5 nm in aqueous condition. In cultured cells, HIFU-treated DOX-CNPs showed rapid drug release and enhanced cellular uptake in A549 cells, resulting in increased cytotoxicity, compared to untreated DOX-CNPs. In ECM-rich A549 tumor-bearing mice, the tumor-targeting efficacy of intravenously injected DOX-CNPs with HIFU treatment was 1.84 times higher than that of untreated DOX-CNPs. Furthermore, the deep tumor penetration of HIFU-treated DOX-CNPs was clearly observed at targeted tumor tissues, due to the destruction of the ECM structure via HIFU treatment. Finally, HIFU-treated DOX-CNPs greatly increased the therapeutic efficacy at ECM-rich A549 tumor-bearing mice, compared to free DOX and untreated DOX-CNPs. This deep penetration of drug-loaded nanoparticles via HIFU treatment is a promising strategy to treat heterogeneous tumors with dense ECM structures.